Literatur Review: Pengaruh Kualitas Produk, Harga dan Loyalitas terhadap Kepuasan Konsumen Kopi Nako - Sabrina Luna Rahellea; Muhammad Richo Rianto (Studi Ilmu Manajemen dan Organisasi, 2023)
Purpose: This study aims to determine the effect of product quality, price and loyalty on Nako coffee consumer satisfaction. Methodology: This study uses the "Literature Review" method using Google Scholar to obtain data from online journal article literature. Results: The results of this study indicate that product quality, price and loyalty have a significant effect on customer satisfaction of Nako coffee. Limitations: This research was only conducted on Nako coffee consumers. These variables include product quality, price and loyalty to see the effect on customer satisfaction of Nako coffee. Contribution: The researcher hopes that this research can provide an overview to the company about the conditions that are currently happening in the company, and hope to provide insight into managing the company and creating good quality so that it can have a positive influence on customer satisfaction.